A BUMPY ROAD TO YOUTH: A CROSS SECTIONAL SURVEY TO ASSESS EMOTIONAL AND BEHAVIORAL ISSUES OF CHILDREN OF PESHAWAR - Sethi, Mifrah Rauf; Jahangir, Farhana; Irshad, Erum; Irfan, Muhammad (Journal of Postgraduate Medical Institute, 2023)
Objective: To determine the prevalence of Emotional and Behavioral problems in school-aged children of Peshawar Pakistan. Methodology: A cross-sectional survey was conducted on students with the age range of 10-13 years from different private institutions of Peshawar from January to June 2022. The strength and difficulty questionnaire was used to check the emotional and behavioral problems of children along with demographic information. Analysis was done using SPSS v.26 and the results of a test of significance were considered significant at p<0.05 level. Results: The response rate was 93%, with the mean age (n=2053) of 12.45 + 0.79 years. The Reliability of the scale strength and difficulty Questionnaire (SDQ) through Cronbach Alpha reliability was 0.668. The majority of the students were boys (n=1768,86.1%), middle born (n=1924, 93.7%), and belonged to middle socio-economic status (n=2027, 98.7%) respectively. According to the responses on the strength and difficulty questionnaire (SDQ), the prevalence rate was 27.6% (n=566) as abnormal cases. Regarding gender difference, a significant result found that males have more conduct, hyperactivity, and peer problems (p= 0.000) than females. A statistically significant relationship was found in self-reported SDQ among age, gender, birth order, and educational level (p=0.000) through Linear regression analysis. Conclusion: It is estimated that almost one-third of the children reported emotional and behavioral problems. Furthermore, males had a higher level of behavioral problems, while females had more emotional problems.